Romans - Hahn, Scott 1957-; Mitch, Curtis 1970- (Grand Rapids, Michigan Baker Academic, a division of Baker Publishing Group, 2017)
The Messiah and the Gospel of Salvation (1:1-32) -- The Judgment and the Law of God (2:1-29) -- Judgment on Sin and Justification in Christ (3:1-31) -- The Faith and Fatherhood of Abraham (4:1-25) -- Reconciliation in Christ the New Adam (5:1-21) -- New Life and Liberation in the Messiah (6:1-23) -- The Law of Moses and the Law of Sin (7:1-25) -- The Law of the Spirit and the Love of God (8:1-39) -- God's Faithfulness to Israel (9:1-33) -- Israel's Response to the Gospel (10:1-21) -- God's Mercy for All (11:1-36) -- A New Way of Worship and Life in Christ (12:1-21) -- Faithful Citizenship and Fulfillment of the Law (13:1-14) -- The Weak and the Strong in Rome (14:1-23) -- Paul's Final Appeal and Future Plans (15:1-33) -- The Conclusion to Romans (16:1-27).
In this addition to the successful Catholic Commentary on Sacred Scripture (CCSS) series, Scott Hahn, a bestselling author and a leading Catholic interpreter of Scripture, examines Romans from within the living tradition of the Church for pastoral ministers, lay readers, and students alike. The CCSS relates Scripture to Christian life today, is faithfully Catholic, and is supplemented by features designed to help readers understand the Bible more deeply and use it more effectively in teaching, preaching, evangelization, and other forms of ministry. Supported by leading Catholic scholars as well as popular Bible teachers, the series offers a unique level of commentary for Catholic students of the Bible. Its attractive packaging and accessible writing style make it a series to own--and to read! Drawn from the best of contemporary scholarship, series volumes are keyed to the liturgical year and include an index of pastoral subjects
Includes bibliographical references and indexes
Keywords: Catholic Church -- Doctrines; Bible -- Commentaries; Catholic Church; Bible; Theology, Doctrinal; Commentaries